Principal selection for Qatar's government schools: Policy makers', principals' and teachers' perspectives. (September 2020) - Romanowski, Michael H; Sadiq, Hissa; Abu-Tineh, Abdullah M; Ndoye, Abdou; Aql, Mofed
Research indicates that principals are critical in school reform since the implementation of policies and practices is to a large extent determined by the role that principals play in educational change. This study examines the principal selection process used in Qatar for the government schools and identifies knowledge and skills necessary for effective principals from the perspectives of policy makers, principals and teachers working in these schools. Qualitative interviews were held with three policy makers, 21 principals and 82 teachers in focus groups. Findings provide insight into the principal selection process and demonstrate that principals should develop their decision-making skills, should advance as instructional leaders and, since government schools are very diverse, principals must be able to manage issues of nationality, culture and equality. Recommendations are offered to improve the principal selection process for principals working in Qatar or other countries in the Gulf Region.